2019
DOI: 10.1111/petr.13620
|View full text |Cite
|
Sign up to set email alerts
|

Maternal experiences of caring for a child with a ventricular assist device

Abstract: The purpose of this study was to gain a deeper understanding of maternal experiences of caring for their child with a VAD at home as a bridge to transplant. A descriptive, qualitative study was conducted via telephone‐recorded guided interviews. Participants were caring for or had a child with a VAD between 4 and 16 years old. Data collection occurred over a 12‐month period. Using the snowball sampling technique, a purposeful sample of mothers (n = 6) was consented and completed the interview. The data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…The majority of studies established inclusion criteria and consistent selection procedures (n = 12; 75%), [20][21][22][23][24][25][26][27][28][29][30][31] defined the study population, including time period and geographical location of recruitment (n = 11; 69%), 20,21,[23][24][25][26][27][28][29][30][31] and utilized defined outcomes with validated measures (n = 11; 69%). 20,21,23,24,26,27,29,[31][32][33][34] Ten studies (63%) reported a participation rate of greater than 50%, [20][21][22][23][24][25][26][27]29,31 though the remaining six studies did not report participation or attrition results. Notably, few studies justified sample size or utilized effect sizes (n = 4; 25%), 21,29,30,…”
Section: Study Quality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of studies established inclusion criteria and consistent selection procedures (n = 12; 75%), [20][21][22][23][24][25][26][27][28][29][30][31] defined the study population, including time period and geographical location of recruitment (n = 11; 69%), 20,21,[23][24][25][26][27][28][29][30][31] and utilized defined outcomes with validated measures (n = 11; 69%). 20,21,23,24,26,27,29,[31][32][33][34] Ten studies (63%) reported a participation rate of greater than 50%, [20][21][22][23][24][25][26][27]29,31 though the remaining six studies did not report participation or attrition results. Notably, few studies justified sample size or utilized effect sizes (n = 4; 25%), 21,29,30,…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…Notably, few studies justified sample size or utilized effect sizes (n = 4; 25%), 21,29,30,35 and few statistically considered potential confounding variables in analyses (n = 4; 25%), 21,23,26,29 though six studies utilized qualitative data and thematic analyses, and thus statistical assessment of confounding variables was rated NA. 22,25,28,30,33,35 Based on the results of this quality assessment, 50% of included studies were rated as "good" quality (n = 8) 20,21,23,24,26,27,29,31 and 50% of included studies were rated as "fair" quality (n = 8). 22,25,28,30,[32][33][34][35] No studies were excluded from the current literature reviewed based on the quality assessment.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations